Makna Asosiatif dalam Lagu Lihat Kebunku (Taman Bunga) Karya Aku Jeje: Kajian Semantik - Gracella, Arinda; Suseno, Asterina Akbariani; Rahmania, Firli Azkiya; Juansah, Dase Erwin; Firmansyah, Dodi (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This study aims to describe the types and functions of associative meanings in the lyrics of the song